2017
DOI: 10.1155/2017/2704532
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Icariin on the Development of Preimplantation Mouse Embryos against Hydrogen Peroxide‐Induced Oxidative Injury

Abstract: During in vitro cultivation of preimplantation embryos, the balance between ROS production and clearance is disturbed and may lead to incompetent embryos, which might be a main reason of IVF-ET failure. Icariin (ICA) is reported to be active in clearing ROS. The present study aimed to investigate whether ICA could reverse H2O2 pretreatment-induced mouse preimplantation embryo development arrest and, furthermore, to study the underlying mechanisms by detecting ROS levels, mitochondrial membrane potential (ΔΨm),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…Previous studies show that ICA reversed ROS damage in duced by H 2 O 2 treatment in mouse embryos [ 11 ]. In addition, ICA inhibits ROS production in lipopolysaccharide-treated microglia [ 12 ], and could inhibit H 2 O 2 -induced human umbilical vein endothelial injury [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that ICA reversed ROS damage in duced by H 2 O 2 treatment in mouse embryos [ 11 ]. In addition, ICA inhibits ROS production in lipopolysaccharide-treated microglia [ 12 ], and could inhibit H 2 O 2 -induced human umbilical vein endothelial injury [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICA, a kind of plant-derived agent, has received considerable attention for its potential to serve as a substitute therapy for the treatment of OA. ICA exhibits antioxidative properties in various diseases,52–54 including diabetes and osteoarthritis. These findings suggest that ICA may have therapeutic potential for the promotion of ECM synthesis, which is significant to the treatment of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we cryopreserved NPMSCs with ICA at a concentration of 25 μ M. But when we elevated the concentration of ICA to 50 μ M, the cell protective effect of ICA dropped. Some previous studies suggested that appropriate levels of ROS play important roles in normal biological processes [ 21 , 51 ]. The reduced protective effect might be related to the excessive ROS-scavenging function of ICA at high concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Icariin (ICA) is a main active ingredient extracted from the stem leaf of Epimedium brevicornum Maxim [ 17 ], and its chemical structure is shown in Figure 1 [ 18 , 19 ]. A large number of in vitro and in vivo studies suggested that ICA could scavenge reactive oxygen species (ROS) [ 20 ] and exert antioxidative function in protecting the brain and heart [ 21 23 ]. Furthermore, ICA demonstrated other extensive pharmacological effects such as antiapoptosis effect, reproductive effect, anti-inflammation effect, and immunoprotective effect [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%